Simulating Weather Events on a Real-world Map using Unity 3D - Noueihed, Hamza (2022)
During the past decade, 3D simulation models have gained importance in the development of software solutions that aim to mimic real-world events and phenomena with increasing levels of accuracy and detail. In this paper, we introduce VOWES, a Virtual Outdoor Weather Event Simulator to replicate and measure outdoor weather events in vivid 3D visualizations. We make use of the Unity 3D engine to build the simulator environment and its virtual sensors, and integrate the Mapbox SDK and the WeatherStack API for realistic real-world weather mapping. We have conducted a large battery of experiments involving 30 human testers, considering various evaluation criteria. Results highlight VOWES’ quality and performance, and its ability to simulate complex weather environments with large numbers of sensors and weather phenomena.